2010
DOI: 10.1007/s10384-010-0855-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of brimonidine 0.2%-timolol 0.5% fixed-combination therapy for glaucoma

Abstract: The results of this study suggest that brimonidine/timolol fixed-combination therapy has beneficial IOP-lowering effects and significant effects on pupil size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Improved adherence has also been reported as compared to the use of either travoprost or timolol separately [11][12][13]. However, as little time has passed since the TTFC and other fixed-combination therapies have been approved for glaucoma, there is as yet little information available on the use of such combination therapies in Asian glaucoma patients, including Japanese patients, compared to the many reports that focus on Caucasian populations [14].…”
Section: Introductionmentioning
confidence: 94%
“…Improved adherence has also been reported as compared to the use of either travoprost or timolol separately [11][12][13]. However, as little time has passed since the TTFC and other fixed-combination therapies have been approved for glaucoma, there is as yet little information available on the use of such combination therapies in Asian glaucoma patients, including Japanese patients, compared to the many reports that focus on Caucasian populations [14].…”
Section: Introductionmentioning
confidence: 94%
“…Participants were followed for 6 months Chen 2006 Not a randomized trial: prospective case series of patients switched to unoprostone isopropyl ophthalmic solution (Rescula) after initial treatment with beta-blockers. Participants were followed for 1 year Cho 2010 Short-term trial: evaluation of fixed combination of brimonidine 0.2%-timolol 0.5% in people with glaucoma. Participants were followed for up to 6 months CNTGS 1998 Not intervention of interest: included any medical and surgical treatment to lower IOP, and was not limited to the agents listed in the protocol Cohen 2005 Not a randomized trial: review of ocular hypotensive agents for the treatment of glaucoma and ocular hypertension Cordeiro 2011 Not a randomized trial: editorial discussing clinical trials for neuroprotection in glaucoma Costagliola 2014 Short-term trial: RCT of palmitoylethanolamide versus no palmitoylethanolamide in people with NTG.…”
Section: Appendicesmentioning
confidence: 99%
“…Cho et al [34] reported that after instillation with one drop of brimonidine/timolol fixed combination, the largest difference in IOP between treated and untreated eyes 6 hours after instillation was 1.7 mmHg ( p = 0.011). Differences in IOP between instilled eyes and untreated eyes first appeared 4 hours after instillation and were maintained for 14 hours after instillation.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in IOP between instilled eyes and untreated eyes first appeared 4 hours after instillation and were maintained for 14 hours after instillation. However, Cho et al [34] did not measure IOP later than 14 hours after instillation. In the present study, the largest difference in IOP between treated and untreated eyes 8 hours after instillation was 1.67 mmHg in the BTFC group ( p < 0.001).…”
Section: Discussionmentioning
confidence: 99%